Using laser capture microdissection to study fiber specific signaling in locomotor muscle in COPD: A pilot study - Mohan, Divya; Lewis, Amy; Patel, Mehul S.; Curtis, Katrina J.; Lee, Jen Y.; Hopkinson, Nicholas S.; Wilkinson, Ian B.; Kemp, Paul R.; Polkey, Michael I. (Muscle & nerve, 2017)
ABSTRACT Introduction Quadriceps dysfunction is important in chronic obstructive pulmonary disease (COPD), with an associated increased proportion of type II fibers. Investigation of protein synthesis and degradation has yielded conflicting results, possibly due to study of whole biopsy samples, whereas signaling may be fiber‐specific. Our objective was to develop a method for fiber‐specific gene expression analysis. Methods 12 COPD and 6 healthy subjects underwent quadriceps biopsy. Cryosections were immunostained for type II fibers, which were separated using laser capture microdissection (LCM). Whole muscle and different fiber populations were subject to quantitative polymerase chain reaction. Results Levels of muscle‐RING‐finger‐protein‐1 and Atrogin‐1 were lower in type II fibers of COPD versus healthy subjects (P = 0.02 and P = 0.03, respectively), but differences were not apparent in whole muscle or type I fibers. Conclusions We describe a novel method for studying fiber‐specific gene expression in optimum cutting temperature compound‐embedded muscle specimens. LCM offers a more sensitive way to identify molecular changes in COPD muscle. Muscle Nerve 55: 902–912, 2017